Transparansi Dan Akuntabilitas Laporan Keuangan Lembaga Amil Zakat: Perspektif Muzaki Upz Bni Syariah - Indrarini, Rachma (AKRUAL: JURNAL AKUNTANSI, 2017)
AbstractIndonesia is one of country that has great potential zakat. That is because the majority of Indonesia's population is Muslim. But the phenomenon that the opposite is where zakat is not as big as the existing potential. In fact, in Indonesia many Organisasi Penerima Zakat (OPZ) both government and private sector have a good system, professional and trustworthy. Allegedly one of the problems is the lack of transparency and accountability of institutions. The method used in this research is descriptive qualitative data collection techniques used interviews. The object of research is UPZ BNI Syariah. The results of this research are largely muzaki UPZ BNI Syariah not feel the transparency and accountability of UPZ BNI Syariah.